Analisis dan Rekonstruksi Desain Kegiatan Laboratorium (DKL) Uji Makanan Berbasis ANCORB - Zahra, Nadia; Supriatno, Bambang; Anggraeni, Sri (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The practicum method is one of the strategies in learning that includes the cognitive, affective and psychomotor domains as well as a learning activity that aims to give students the opportunity to test and apply theory with facilities using laboratories or outside the laboratory. In practicum, teachers usually use LKPD as a guide for practicum activities. However, based on the results of previous analysis and research, actually only a small portion of the LKPD can be used. The purpose of this research is to analyze and reconstruct the design of food testing laboratory activities. The type of research used is descriptive qualitative and the sampling is done by purposive sampling with a total of 5 DKL. The analysis conducted on DKL is measured in terms of competence, practice, and knowledge construction. The results obtained that the components of competence and knowledge construction are still low, while the practical components are sufficient. This shows that there are still many food tests that cannot support competence and knowledge construction.